Malaysia pre-school animal education virtual reality (VR) application - Roslan, Rosfuzah; Mohd Ayub, Ahmad Fauzi; Zulkifli, Nurul Nadwa (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2023)
Introducing a Virtual Reality (VR) application called VRMiniZoo, a pre-school animal education VR product that is Malaysian Muslim culture-based. Culture-based education is an approach, in which teaching and learning happen based on the values, norms, beliefs and practices that are the foundation of any culture. In Malaysia, it is common to educate the pre-school students on the local culture and mannerism. Pre-school education is considered as an important intervention in a child’s early development in which at this age, their experiences will be sensitive to their future academic and social life. VRMiniZoo creates different teaching scenarios and approaches in animal education for the pre-school students, providing an alternative to the conventional method of physical ‘field trips’ by implementing VR and gamification aspects of the MDA framework. The Mechanics Dynamics Aesthetics (MDA) is a formal approach in correlating gaming design elements with software deliverables. Through the successful implementation of the basic VRMiniZoo application (Version 1) at one of the Malaysian Islamic pre-school or Early Learning Center (ELC), the teachers agreed that the VRMiniZoo is able to serve as an assisting tool. The tool contributed in giving understanding of the children’s reactions, motivation, and engagement in their animal topic learning session. Moreover, with VR the children are able to think creatively when immersed in a new environment while staying in comfortable settings such as at home or school.